2019
DOI: 10.1111/jace.16301
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of pore formation and resulting properties of lightweight inorganic polymers

Abstract: Inorganic polymer (IP) foams could be used as an alternative to commonly available cellular concretes. To do so, however, it is crucial to understand how the foaming kinetics and the final foam properties can be controlled and tailored to delivered the desired performance. The research reported in this article investigates the influence of the SiO 2 /Na 2 O ratio of the activating solution, addition time of foaming agent, and temperature, on the reaction kinetics and final properties of a porous IP. The IPs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In comparison with previous studies, the timing of the maximum of the exotherm is similar, taking into account the activating solution that was used. The absolute values of the cumulative heat of the three samples are comparable to other Fe‐rich slags …”
Section: Resultssupporting
confidence: 52%
“…In comparison with previous studies, the timing of the maximum of the exotherm is similar, taking into account the activating solution that was used. The absolute values of the cumulative heat of the three samples are comparable to other Fe‐rich slags …”
Section: Resultssupporting
confidence: 52%
“…This measurement of heat released by FF is consistent with other iron-rich slags activated with similar alkaline solutions, as reported in the literature. 32,39,40 In both paste samples, the reaction continues after 96 h, as by this point, the cumulative heat released is still increasing. The continuation of the reaction was found to induce microstructural evolution at the later ages.…”
Section: 2mentioning
confidence: 88%
“…Henon et al observed higher and faster expansion when increasing temperature [101]. Denissen et al also reported that increasing temperature causes faster foaming [100]; however, the influence of temperature was dependent on the SiO 2 /Na 2 O: higher ratios led to greater expansion at higher temperatures, but when using a low SiO 2 /Na 2 O ratio, the highest volume expansion was achieved at 20-25 °C. This behaviour was attributed to the complex interaction between foaming kinetics, setting time and the physical properties of the paste.…”
Section: Thermal and Acoustic Insulatorsmentioning
confidence: 97%
“…Curing temperature [100,101] and activator concentration [102] can also be used to control foaming kinetics and setting time. Henon et al observed higher and faster expansion when increasing temperature [101].…”
Section: Thermal and Acoustic Insulatorsmentioning
confidence: 99%